ANALISIS POLA SEBARAN DEMAM BERDARAH DENGUE (DBD) DENGAN PENDEKATAN SPASIAL DI KOTA PEKANBARU - Lesi Kurnia Putri; Rahman Karnila; Zahtamal Zahtamal (Program Pascasarjana Universitas Riau, 2019)
Environmental, behavioral, health service, genetic and demographic determinants of health that can affect people’s health. The environmental change triggered by global warming and greenhouse effect is happening can include icreased temperature, rainfall and humidity. Dengue Hemorrhagic Fever (DHF) is a vector disease related to climate change and population density. The high population density could transmitting the virus from one person to other person in the vicinity. The purpose of this research is to describe of the DHF with a spatial analysis in Pekanbaru city. The design of this research is an ecological study to describe of temperature, rainfall and humidity to the incidence of DHF and population density using spatial analysis. The results showed the existence of spatial analysis indicate areas with high population density were not found in high cases of DHF. Other risk factors statistically not associated with DHF are temperature (p=0.54, r=0.105), rainfall (p=0.63, r=0.083) and humadity (p=0.41, r=0.083).